PENDIDIKAN DAN PELATIHAN KADER JUMATIK DESA SUMBERTEBU DI ERA ADAPTASI KEBIASAAN BARU PANDEMI COVID-19 - Dwi Helynarti Syurandhari; Arief Fardiansyah; Asih Media Yuniarti; Mukhammad Himawan Saputra; Yusuf hariyadi; Rifaatul Laila Mahmudah; Rahmi Syarifatun Abidah (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2021)
The public and health teams in Indonesia focus on handling and preventing Covid-19 during the Covid-19 pandemic, on the other hand, the number of dengue cases has actually increased. The purpose of education and training for Jumantik Cadre in Sumbertebu Village, Bangsal District, Mojokerto Regency as a form of community service carried out by the Lecturer and Student Team of the Majapahit Health Sciences College is to provide encouragement and refreshment to jumantik cadres in running again while following health procedures in the Adaptation Era. New Habits of the Covid-19 Pandemic Education and training efforts are carried out using the lecture method and PLA or Participatory Learning and Action, this method allows for community empowerment efforts, especially jumantik cadres. The community service participants were 21 jumantik cadres. The activity which was carried out for almost 1 month was able to increase the knowledge and understanding of jumatic cadres in carrying out supervision and eradication and implementation in strengthening community behavior. This activity is expected to increase the motivation of jumantik cadres to carry out their duties again so that dengue cases do not occur again.